Towards Sustainable Revitalization: The Public Squares Characteristics - Led the Adaptive Urban Revitalization Mechanisms - Zakariya Osamaa Ibrahim; Sally Fakhri Khalaf Abdullah (Salehan Institute of Higher Education, 2023)
The public square is a specifically designed urban space that includes many natural and formative elements that achieve communication among the main axes of the city and facilitate the movement of users through it. The public squares (PSs) in many cities, especially Baghdad, need to be revitalized. The Adaptive Urban Revitalization (AUR) strategy, which focuses on improving the quality of urban spaces for PSs to enhance their location, activity, and purpose, can be used for this revitalization. The result is a new space that is adaptive and convenient with regard to the sustainable revitalization of the contemporary city. The main research problem is how to make PSs attractive places for users. There is an absence of clear knowledge about the mechanisms of the AUR strategy, its relationship to the characteristics of PSs, and its influence on the revitalization process. Considering this problem, the main research goal is to reveal the characteristics of PSs as factors that affect the mechanisms of AUR and the role that these influences have in developing a clear approach to the AUR strategy to make PSs attractive places for users. This can be done by improving their conditions and promoting their use more effectively. To achieve this goal, the research will address improving the quality of urban spaces through the application of the AUR strategy. The focus is on addressing urban problems that have an effect on PSs, obtaining the indicators of AUR, applying them to the selected case studies and testing them mathematically. The results of the research produced a clear approach with regard to utilizing the strategy of AUR in PSs. It examined all mechanisms represented by Urban Response, Urban Accessibility, and Dynamic Activities. The results showed a positive relationship of these mechanisms on the characteristics of PSs. Doi: 10.28991/CEJ-2023-09-04-015 Full Text: PDF